2017
DOI: 10.3389/fmicb.2017.01975
|View full text |Cite
|
Sign up to set email alerts
|

Soil Viral Communities Vary Temporally and along a Land Use Transect as Revealed by Virus-Like Particle Counting and a Modified Community Fingerprinting Approach (fRAPD)

Abstract: Environmental surveys on soil viruses are still rare and mostly anecdotal, i. e., they mostly report on viruses at one location or for only a few sampling dates. Detailed time-series analysis with multiple samples can reveal the spatio-temporal dynamics of viral communities and provide important input as to how viruses interact with their potential hosts and the environment. Such surveys, however, require fast, easy-to-apply and reliable methods. In the present study we surveyed monthly across 13 months the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 91 publications
0
38
1
Order By: Relevance
“…We also investigated the impact of agriculture on soil viral AMGs. We predicted that cultivation would shift the composition of soil viromes due to shifts in soil properties such as pH, total nitrogen content, and fertilizer application, as previously demonstrated 5,6,13,35,36 .…”
Section: Auxiliary Metabolic Genes (Amgs)mentioning
confidence: 85%
See 1 more Smart Citation
“…We also investigated the impact of agriculture on soil viral AMGs. We predicted that cultivation would shift the composition of soil viromes due to shifts in soil properties such as pH, total nitrogen content, and fertilizer application, as previously demonstrated 5,6,13,35,36 .…”
Section: Auxiliary Metabolic Genes (Amgs)mentioning
confidence: 85%
“…A global meta-analysis of viral distribution revealed that the vast majority of viruses are clearly habitat-specific 3 . The soil virome in particular is poorly characterized in terms of its size and composition, but limited evidence shows that soil viruses are more abundant and diverse than viruses from other ecosystems 4,5,6 . This high viral diversity may be a result of the heterogeneous physical matrix of soil where spatial structuring generates a plethora of environmental niches 7,8 .…”
mentioning
confidence: 99%
“…Soils’ heterogeneity in texture, mineral composition, and OM content results in significant inconsistency of yields from standard virus ‘capture’ methods (3639). While many soils contain large numbers of viral particles (10 7 –10 9 virus particles per gram of soil; 37, 4042), knowledge of soil viral ecology has come mainly from the fraction that desorb easily from soils (<10% in 43) and the much smaller subset that have been isolated (44).…”
Section: Introductionmentioning
confidence: 99%
“…It is still unclear how soil characteristics and ecosystem management practices affect viral communities. Fertilizer application has been reported to increase the abundance of viruses (Chen et al, 2014) and temporal variability in forest and arable soils (Narr et al, 2017). Viral communities are very dynamic as viruses have extreme evolutionary capacities and high genetic diversity that have allowed them to parasitize all known groups of organisms and to rapidly adapt to numerous host species.…”
Section: Discussionmentioning
confidence: 99%